Factors Influencing a Thai Individual’s Trust and Distrust in Social Commerce - Porntrakoon, Paitoon (Humanities, Arts and Social Sciences Studies, 2019)
The purpose of this research is to study the factors influencing trust and distrust of Thai people in using social commerce and the moderating effects on those factors. A theoretical model is developed including groups of factors derived from previous studies (social commerce constructs, characteristics of social media websites, characteristics of e-vendors, personality traits of consumers, and Thai culture) with direct effects on both trust and distrust which are treated as distinct constructs rather than as opposite ends of a continuum of measurement. Also, the model includes gender, education, age, and social commerce experience as factors that moderate the direct effects. The model is analyzed and developed with descriptive statistics and structural equation modeling using data collected by questionnaire from 662 Thai social commerce users. The ability of an e-vendor to supply the expected products and services emerged as the most important influence on trust while the personality trait neuroticism had the most important influence on distrust. Gender, age, and social commerce experience were found to have moderating effects on some causal effects while and individual’s level of education did not have any significant moderating effects. New findings concerned the causal effects of several variables (community, perceived ease of use, competence, reputation and integrity, quality of information, agreeableness, conscientiousness, and relationship orientation) and the moderating effects of gender, education, age, and social commerce experience. Theoretical and practical implications of the findings are discussed in detail.